Identification of Kasiuluran Culture in the Formation of the Character Value of Tolerance in Grade V Students of SDN 55 Patudu of Gadangbatu Sillanan District - Irene Hendrika Ramopoly; Charlie Baka (Edumaspul: Jurnal Pendidikan, 2022)
This study aims to describe the culture of Kasiuluran for the formation of the character values ​​of tolerance in students at SDN 155 Patudu, Gandangbatu Sillanan District. This type of research is descriptive qualitative research. Informants in this study were fifth grade teachers and fifth grade students. Data collection procedures included observation, interviews, and documentation. Data analysis uses data reduction steps, and drawing conclusions. After this research was conducted, it was found that the Kasiuluran culture is a close kinship relationship from time to time, both those who have blood relations and those who are not, known as solata which means fellow who will unite everyone wherever they are, so that a sense of brotherhood is created. make the community share as fairly as possible according to the rights and portions that should be. From the results of the study, it is known that the culture of kindness can shape the character of tolerance in class students, namely students respect each other. This can be seen from the way the teacher teaches who always invites students to respect each other's religious differences, and respect older people. In addition, this is also seen in the kasiuluran culture where there are values ​​of tolerance character, among others: 1) Sipopa'di'-kasipopa'diran contains a peaceful aspect; 2) Siangga' na sikasiri'-kasianggaran, Sisipa'- kasisiparan or pessiparan, contains aspects of respecting differences; 3) Sidikkan-kasidikkan, Siangkaran Sikamali' values, contains aspects of individual awareness.